NANOCÁPSULA DE DIHIDROMIRICETINA: PERFIL DE SEGURANÇA E EFICÁCIA IN SÍLICO E IN VITRO FRENTE A DISFUNÇÃO MITOCONDRIAL E NEUROINFLAMAÇÃO RELACIONADAS AO TRANSTORNO BIPOLAR - Ramos, Andiara Prates (2024)
Bipolar disorder (BD), like other neuropsychiatric disorders, is related to mitochondrial dysfunction and inflammatory and neuroinflammatory processes, these processes being potential therapeutic targets. Flavonoids can be a promising alternative, in this context, dihydromyricetin (DHM) is a flavonoid that presents several pharmacological properties with emphasis on antioxidant, anti-inflammatory and cytoprotective activities. However, DHM presents instability resulting from environmental exposure, a fact that can compromise its pharmacological functionality. The objective of this work was to use in silico approaches to identify and improve the aspects that reduce the action of DHM in its free form, as well as to investigate its possible interaction with the NLRP3 inflammasome. Therefore, produce DHM nanocapsules (NC-DHM) and evaluate the in vitro safety profile in neuronal cells (SHSY-5Y lineage) and microglial cells (BV-2 lineage). Subsequently, evaluate its potential biological effect using two cellular damage models: Mitochondrial dysfunction model in a monoculture of SH-SY5Y cells and in a co-culture with SH-SY5Y and BV-2 cells; Model of inflammatory damage induced by lipopolysaccharide (LPS) in a monoculture of BV-2 cells. The results indicated, through in silico analyses, that DHM in its free form has low bioavailability due to its physicochemical characteristics. However, the compound demonstrated an important antioxidant potential and, according to the molecular docking study, binding affinity to the NLRP3 inflammasome. The results regarding the production of NC-DHM were consistent with nanoscale materials. Safety profile assessments demonstrated no cytotoxicity in cells of the SH SY5Y and BV-2 lineage, at different incubation times, when exposed to suspensions of NC DHM and white nanocapsules (NB), except at 50 μg/mL- 1 , highest concentration tested. In the treatment with nanocapsules in SHSY-5Y cells, as well as in co-culture exposed to rotenone, they indicated that the treatment with NC-DHM was superior to free DHM. However, in the model using LPS as an inflammatory inducer in microglial cells, NC-DHM were not able to reverse the effects of this agent on cell viability and proliferation, as well as on the levels of markers linked to cellular oxidative metabolism. However, even with lower levels of reactive oxygen species (ROS) in both damage models, these were not similar to the negative control. It is believed that these results with low efficacy are due to the great instability of DHM even after being nanoencapsulated, making it necessary to improve these aspects, considering its great antioxidant potential.